Electrocatalysis‐driven sustainable plastic waste upcycling - Gaihong Wang; Zhijie Chen; Wei Wei; Bing‐Jie Ni (Electron)
Abstract With large quantities and natural resistance to degradation, plastic waste raises growing environmental concerns in the world. To achieve the upcycling of plastic waste into value‐added products, the electrocatalytic‐driven process is emerging as an attractive option due to the mild operation conditions, high reaction selectivity, and low carbon emission. Herein, this review provides a comprehensive overview of the upgrading of plastic waste via electrocatalysis. Specifically, key electrooxidation processes including the target products, intermediates and reaction pathways in the plastic electro‐reforming process are discussed. Subsequently, advanced electrochemical systems, including the integration of anodic plastic monomer oxidation and value‐added cathodic reduction and photo‐involved electrolysis processes, are summarized. The design strategies of electrocatalysts with enhanced activity are highlighted and catalytic mechanisms in the electrocatalytic oxidation of plastic waste are elucidated. To promote the electrochemistry‐driven sustainable upcycling of plastic waste, challenges and opportunities are further put forward.